Kelayakan E-Modul pada Materi Sistem Pernapasan pada Manusia Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis - Sholikah, Fitriatus; Mawartiningsih, Lilik (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Critical thinking is a 21st-century skill that is crucial for problem-solving and decision-making. However, the learning process in schools is still not optimal in developing this skill. This study aims to test the validity of an e-module product developed to improve critical thinking skills. This research is a developmental study using the 4D model. The instrument used was an expert validation sheet. Data collection was carried out through a questionnaire in the form of a validation sheet given to the validators. Data were analyzed quantitatively based on the validation results, then elaborated with qualitative analysis. The results showed that the material validity value from the three validators was 88.47%, language validity was 89.33%, and media validity was 87.33%. These three results were then averaged, resulting in an overall validity value of 88.37%, which is categorized as valid. Input from the three validators was used as a reference for improving the e-module. Thus, it can be concluded that the e-module on the human respiratory system based on problem-based learning to improve critical thinking skills is valid and worthy of being tested.